Respuesta :
ANSWER
The solution to the system is
[tex]x=5,y=-5[/tex]
EXPLANATION
The system of equations are:
[tex]3x + 2y - 5 = 0 - - (1)[/tex]
and
[tex]x = y + 10 - - (2)[/tex]
We put equation (2) in to equation (1) to get,
[tex]3(y + 10) + 2y - 5 = 0[/tex]
We expand the parenthesis to obtain,
[tex]3y + 30 + 2y - 5 = 0[/tex]
We group like terms to obtain,
[tex]3y + 2y + 30 - 5 = 0[/tex]
[tex]5y + 25 = 0[/tex]
This implies that,
[tex]5y = - 25[/tex]
We divide through by 5 to get
[tex]y = - 5[/tex]
We substitute the value of y in to equation (1) to get,
[tex]3x + 2( -5 ) - 5 = 0 [/tex]
[tex]3x - 10- 5 = 0 [/tex]
This implies that
[tex]3x = 15 [/tex]
We divide both side by 3 to get,
[tex]x = 5[/tex]
The solution to the system is
[tex]x=5,y=-5[/tex]
EXPLANATION
The system of equations are:
[tex]3x + 2y - 5 = 0 - - (1)[/tex]
and
[tex]x = y + 10 - - (2)[/tex]
We put equation (2) in to equation (1) to get,
[tex]3(y + 10) + 2y - 5 = 0[/tex]
We expand the parenthesis to obtain,
[tex]3y + 30 + 2y - 5 = 0[/tex]
We group like terms to obtain,
[tex]3y + 2y + 30 - 5 = 0[/tex]
[tex]5y + 25 = 0[/tex]
This implies that,
[tex]5y = - 25[/tex]
We divide through by 5 to get
[tex]y = - 5[/tex]
We substitute the value of y in to equation (1) to get,
[tex]3x + 2( -5 ) - 5 = 0 [/tex]
[tex]3x - 10- 5 = 0 [/tex]
This implies that
[tex]3x = 15 [/tex]
We divide both side by 3 to get,
[tex]x = 5[/tex]